PENGARUH INFORMASI AKUNTANSI TERHADAP RETURN SAHAM (Studi Pada PerusahaanLQ-45 Di Bursa Efek Jakarta) - Norsain Norsain (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2016)
The use of financial information through the financial statements as a result of an accounting process in the company is an important information in analyzing investment returns in the long term. Through this analysis the investor will be able to assess the ability of a company's profitability, the quality of management performance, as well as future prospects of the company.               Data used in this study is panel data, which is a combination of cross section and time series data 45 company financial statements as sample the period 2010 to 2013. The data sources used mainly in this research is secondary data, including data in the form of documents and information relating to the object of a study published by the Indonesia Stock Exchange through the authority of Capital Market information Center accessed from the official website of the Stock Exchange.               Once the data is collected, the data were analyzed using Eviews program for this type of panel data. Beginning with the analysis of model selection, and then proceed with the classical assumption. The results of the study variables X1 Price Earning Ratio (PER), no effect on variable Y (stock returns), Variable X2 Price to Book Value (PBV) have a significant effect on the variable Y (stock returns), Variable X3 Return on Assets (ROA) significantly the variable Y (stock return). Simultaneously variable PER, PBV, ROA significant effect on the level of α = 10%.Keywords: PER, PBV, ROA, Stock Return